Brokers and business cycles: Does financial market volatility cause real fluctuations? - Jörg Döpke; Christian Pierdzioch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
This paper elaborates on the link between financial market volatility and real economic activity. Using monthly data for Germany from 1968 to 1998, we specify GARCH models to capture the variability of stock market prices, of the real exchange rate, and of a long-term and of a short-term rate of interest and test for the impact of the conditional variance on the future stance of the business cycle and on the volatility of industrial production. The results of our empirical investigation lead us to reject the hypothesis that financial market volatility causes the cycle or real volatility.
Keywords: C32; D8; E32; 330; Uncertainty; GARCH models; forecasting; Granger-non-causality; causality-in-variance; Konjunktur; Finanzmarkt; Volatilität; Schätzung; Börsenkurs; Wechselkurs; Zins; Industrielle Produktion; Deutschland